Acute and Chronic Respiratory Effects of Chromium Mists - Masoud Neghab; Parisa Azad; marzieh Honarbakhsh; Fatemeh Zarei; Ebrahim Ghaderi (Shiraz University of Medical Sciences, 2015)
Background: Despite wide application of chromium in electroplating industry, the pulmonary effects of chronic exposure to this chemical have not been extensively studied and are subject of debate and controversy. This study was, therefore, undertaken to further address this issue. Methods: The study population consisted of a group of 15 workers with a history of past and present occupational exposure to chromium mists and 15 unexposed healthy subjects (referent). Subjects were interviewed, respiratory symptom questionnaires were filled out for them, and their parameters of pulmonary function (PFT) were measured during the shift and a few days after exposure ceased. Results: Both groups were similar as to the number of smokers, their length of smoking, and demographic factors such as age, weight and height. Although the unexposed group, on average, were slightly older than their exposed counterparts, statistical analysis of the data revealed that symptoms such as productive cough, phlegm, wheezing and shortness of breath were significantly (P<0.05) more prevalent among the exposed workers. Furthermore, the parameters of pulmonary function (PFT) of the exposed workers, while at work, were significantly lower than those of referent individuals. Interestingly, PFT of the exposed subjects generally showed some improvement a few days after their exposure ceased. However, despite this relative recovery, the differences of PFT values between the exposed and referent groups, from statistical point of view, remained significant. Conclusion: Our data support the proposition that exposure to chromium mists induces abnormal respiratory symptoms as well as both acute, partially reversible and chronic irreversible lung functional impairments.